2013
DOI: 10.15835/nsb518038
|View full text |Cite
|
Sign up to set email alerts
|

Lead Toxicity and The Hypothalamic-Pituitary-Testicular Axis

Abstract: Environmental exposure to toxic levels of lead (Pb) occurs in a number of industries with potential adverse effects on the reproductive capacity of exposed men. Clinical and animal studies indicate that abnormalities of spermatogenesis result from toxic lead exposure, but eventual histopathologic alterations involved have not been identified. To explore putative abnormalities in the reproductive gonadotropic axis following lead intoxication, experimental animals when exposed to low levels of lead, 65 days old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…At the testicular level, lead impairs testicular LH receptor concentrations and steroidogenesis at the pubertal stage (Ronis et al , 1996). Another animal study with lead exposure during sexual development showed degenerative changes in gonadotropic cells of the pituitary gland, thus accounting for suppressed plasma LH and testosterone levels into adulthood (Ait Hamadouche et al , 2013).…”
Section: Lead Toxicity and The Hypothalamic-pituitary-testicular Axismentioning
confidence: 99%
See 2 more Smart Citations
“…At the testicular level, lead impairs testicular LH receptor concentrations and steroidogenesis at the pubertal stage (Ronis et al , 1996). Another animal study with lead exposure during sexual development showed degenerative changes in gonadotropic cells of the pituitary gland, thus accounting for suppressed plasma LH and testosterone levels into adulthood (Ait Hamadouche et al , 2013).…”
Section: Lead Toxicity and The Hypothalamic-pituitary-testicular Axismentioning
confidence: 99%
“…ROS halts synthesis of sulfhydryl antioxidants and prevents enzymatic reactions (Vigeh et al , 2011). In fact, lead itself has high affinity to sulfhydryl residues in proteins, thus acting as a nonspecific enzyme inhibitor and arresting their antioxidant activity (Ait Hamadouche et al , 2013). As oxidative stress disturbs chromatin condensation, it has been suggested that the under-protamination of sperm DNA could automatically lead to DNA fragmentation (Henkel et al , 2010).…”
Section: Lead Toxicity and The Hypothalamic-pituitary-testicular Axismentioning
confidence: 99%
See 1 more Smart Citation
“…EST is also essential for spermiogenesis. (13) The strong negativity observed in the correlation of TESTO and EST with toxic metals shows the effect of the toxic metals on the endocrine functions of the e-waste workers. The workers are therefore at risk of developing pathological conditions that are associated with reproductive endocrine dysfunction, the effect of which may cumulatively lead to sterility and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Derivatives of the amino acid tyrosine, are secreted by the thyroid (thyroxine and triiodothyronine) and the adrenal medullae (epinephrine and norepinephrine. (12,13) Previous studies have shown changes in the concentration of hormones in workers occupationally exposed to heavy metals such as lead (Pb). These changes were proposed to be mediated at the hypothalamic-pituitary level.…”
Section: Introductionmentioning
confidence: 99%